A content analysis of food advertising on Turkish television - Ok, Mehtap Akcil; Ercan, Aydan; Kaya, Fatih Suleyman (Oxford Univ Press, 2016)
The aim of this study was to conduct a comprehensive content analysis of Television (TV) food advertising and compare various food advertisements on free-to-air Turkish national TV channels by broadcast time (duration) and frequency over the period of aweek (19-25 April 2012). TV food advertisements were the unit of content analysis in this study. Each advertisement identified as promoting a food product was analysed for content; non-food advertisements were not analysed, although they were counted as a proportion of the advertisements aired. We recorded all programmes for 4 h each per day (7 p.m.-11 p.m.), totalling 84 h. Five types of food-related advertisements were identified (basic foods, junk foods, meat products, beverages and fast food), and six types of non-food advertisements. The Student t-test and ANOVA were used to compare the mean broadcast time of all prime time advertising for the two groups. The mean broadcast times for prime time, non-food advertisements showed a statistically significant difference (p < 0.05). This difference is related to the prime time period 7 p.m.-8p.m. being considered dinner time for most Turkish families. Additionally, the number and broadcast times of beverage advertisements increased during this time period, while the broadcast time per beverage advertisement decreased (ratio = 20.8 s per ads). As a result, TV food advertising increased not only during dinner time but also in overall broadcast time (per advertisement). These findings may be useful for explaining how advertising can negatively influence food choices, thereby increasing public awareness of the need for health messages targeting obesity.
Keywords: food advertisement; television; adults; Turkey